OG’ZAKI BO’LMAGAN MULOQOTNING MADANIY XUSUSIYATLARI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
As we all know, good knowledge of a foreign language can cause a misunderstanding of the state of the interlocutor, that is, gestures. When starting a conversation with gestures, it is wise to set the main goal to learn the customs of the foreigner and this country. Because communicating through gestures may be contrary to the culture of another country. The content of our article also focuses on gestures and gestures and facial expressions.
Keywords: gesture, behavior, concept, facial expression, interlocutor, ethnography, techniques, cocorroco, handshake, raising an eyebrow, curling lips.